ANALISIS LOKASI IBUKOTA KERAJAAN SRIWIJAYA ABAD 7-8 M - Najuah Najuah; Lulu Luciana Sinurat; Khalishatun Zahra; Akhila Ardianti Nasution; Cahaya Purnama Sari (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
Srivijaya Kingdom is one of the strong maritime kingdoms on the island of Sumatra and has a lot of influence in the archipelago with a wide area of authority. However, in fact the Srivijaya Kingdom was actually the "youngest" kingdom in the archipelago by its invention, because the name of the Srivijaya Kingdom was only "dug up" and surfaced around the beginning of the 20th century after the discovery of several inscriptions. The earliest evidence of the existence of this kingdom comes from the 7th century, a Chinese priest from the Tang Dynasty, I Tsing, wrote that he visited Srivijaya in 671 and stayed for 6 months. Furthermore, the oldest inscription about Srivijaya was also in the 7th century, namely the Kedukan Bukit inscription in Palembang, dated 682. There are many historical sources stating the existence of the Srivijaya Kingdom and its territories. However, there is no single source that clearly tells where the center of this Sriwijaya Kingdom lies. In this case, experts also differed opinions regarding the existence of the center of the Srivijaya Kingdom.